Translation of teamwork survey questionnaire (TSQ) for Malaysian public healthcare services: Process and findings - Sakinah, Harith; Wan Siti Auni, W.S.; Pereira, D.J.; Lim, P.Y. (2017)
Teamwork is a prerequisite for effective healthcare services. However, there is a lack of teamwork assessment tools tailored for developing country services. To provide a tool for teamwork assessment in Malaysian public healthcare services, this study aimed to translate the original English version teamwork survey questionnaire into the Malay language.The teamwork survey questionnaire was previously used for Australian rehabilitation services. The 35 item questionnaire covers teamwork domains representing demographics, integration, efficiency and relationships. The translation process involved: contextual adaptation; two forward translations; reconciliation of the two forward translation Malay versions; back translation into English; reconciliation of back translated tool with original and Malay versions; and face validation with ten respondents. A main reference for researchers was an official Malay language resource website.Contextual adaptation resulted in the questionnaire's statements being generalized for various healthcare services. Two forward translation versions enabled comparison of phrasing and choice of words. Some phrasing showed variation requiring reference to the original English tool to confirm intended meaning of statements. Few Malay statements deviated in meaning from the original English tool due to inappropriate word for word translation. The majority of items in the back translated English version showed similarity of meaning with the original English tool. Differences in the two English versions highlighted mistranslations overlooked during forward translation. Face validation highlighted three demographic questions that could potentially confuse respondents due to a common key word. Researchers decided to provide verbal clarification for the problematic questions before tool administration.Preserving the original tool's purpose while mitigating local language nuances relied upon: translators‟ competence; availability of a reliable language resource; and feedback from target respondents. In adopting this approach for other tools and contexts, additional translator involvement could be required if researchers are not proficient in either a questionnaire's foreign language or the intended local language.